Rural Reforms and Agricultural Growth in China - Lin, Justin Yifu (American Economic Review, 1992)
This paper employs province-level panel data to assess the contributions of decollectivization, price adjustments, and other reforms to China's agricultural growth in the reform period. Decollectivization is found to improve total factor productivity and to account for about half of the output growth during 1978-1984. The adjustment in state procurement prices also contributed positively to output growth. Its impact came mainly from the responses in input use. The effect of other market-related reforms on productivity and output growth was very small. Reasons for slowdown in agricultural growth after 1984 are also analyzed.